Shifting Baselines May Undermine Shoreline Management Efforts in the United States - Correll-Brown, Riordan; Wellman, Emory H.; Eulie, Devon O.; Scyphers, Steven B.; Smith, Carter S.; Polk, Mariko A.; Gittman, Rachel K. (Frontiers in Climate, 2022)
Rising sea levels, extreme weather events, and unsustainable coastal zone development pose serious threats to growing coastal communities. Human actions, such as shoreline development and hardening in at-risk areas, can damage nearshore ecosystems and exacerbate existing risks to coastal populations. A comprehensive understanding of shoreline changes in response to development, storm events, and sea-level rise is needed to effectively mitigate coastal hazards and promote adaptive and resilient coastlines. To determine whether human modification of shorelines can be accurately quantified and assessed over time, we evaluated past and current shoreline mapping and classification efforts in the United States. We coupled a review of available US shoreline data with a survey of coastal planners and managers involved with US state shoreline mapping programs. Using these data, we estimated the current extent of shoreline modification along the Atlantic, Pacific, and Gulf US coasts. However, we found that quantifying shoreline modifications over time nationally — or even within a single state — is currently infeasible due to changes in shoreline resolution associated with advances in shoreline mapping methodologies and a lack of regularly updated shoreline maps. State-level analysis from surveys revealed that 20 US coastal states have undertaken shoreline mapping projects, with sixteen tracking shoreline type and/or condition. However, of the 36 shoreline maps and databases identified, only half (18) were updated regularly or had planned updates. Lacking shoreline change data, coastal communities risk accepting increasingly degraded coastal zones and making poor management decisions based on shifted baselines. Thus, we recommend increasing the scale and funding for several ongoing innovative shoreline mapping efforts. These efforts are particularly focused on improving and standardizing shoreline mapping techniques, as well as establishing accurate baselines for shoreline conditions in the United States. Without accurate baselines and regular, consistent updates to shoreline data, managers cannot manage shorelines in a way that effectively mitigates coastal hazards while also promoting socio-ecological resilience to a changing climate.